Synthesis of some Cd(II) and Zn(II) complexes of a tetraazamacrocyclic ligand and their antimicrobial activities (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Synthetic macrocycles specially the tetraazamacrocycles and their complexes have attracted considerable interests owing to their wide variety of applications. The ligand, 3, 10-C-meso- 3,5,7,7,10,12,14,14-octamethy1-1,4,8,11- tetraazacyclotetradeca-4,11-diene(L1), upon reaction with CdI2, Zn(ClO4)2, and Zn(CH3COO)2 produces corresponding square pyramidal cadmium (II) and zinc (II) complexes of formula [ML1X]Yn, (M = Cd or Zn; X = I, CH3COO or H2O; Y= I, ClO4 or CH3COO; n = 1 or 2). Among them, [CdL1I]I and [ZnL1(H2O)](ClO4)2 undergo substitution reactions with KSCN and NaNO2, respectively to produce octahedral trans- diisothiocyanatocadmium(II) complex, trans-[CdL1(NCS)2] and square pyramidal mononitratozinc(II) nitrate complex, [ZnL1(NO2)](NO2). Antifimgal and antibacterial activities of these complexes against some of phytopathogenic fungi and bacteria have been investigated in this study.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 136-144